Guest Editorial: Privatisation of Information Services - Lahiri, Abhijit (DESIDOC Journal of Library & Information Technology, 2002)
Privatisation is a buzz word today. The term largely refers to the transfer of a part of the ownership of a hitherto fully government owned company to the public or to private enterprises. The process has been on for the last three years in our country. However, truely speaking, the seal motive behind such move was to raise additional financial resources to support developmental needs. In true sense of the term, privatisation would mean transfer of management responsibilities of government companies or governmental activities to private hands. http://dx.doi.org/10.14429/dbit.15.5.3199